Compressive and tensile behavior of AA2014-T6 under different strain rates and different temperatures. (March 2023) - Pandouria, Anoop Kumar; Yadav, Kuldeep; Tiwari, Vikrant
Abstract: This article investigates the quasi-static and dynamic mechanical response of AA2014-T6 alloy under uniaxial compression and tension loading. Influence of strain rate (10 −4 to 2×10 3 s −1 ) and temperatures (25 °C to 250 °C) are also presented in this study. Static experiments have been performed on a conventional UTM, while the dynamic experiments were performed using tensile and compressive split Hopkinson pressure bar setup. It was observed that the plastic flow stress of the material follows the positive strain rate sensitivity over the wide range of strain rates for both kind of loadings. However, it follows the negative sensitivity with increase in temperature. Experimental results also showed that the flow stress gradually decreased uniformly with temperature increases up to 200 °C and beyond that, it is reduced drastically. Also the true fracture strain increased from 14.8 % to 51.5 % when temperature was increased from 25 °C to 250 °C. Material strength achieved during the uniaxial compression experiments is found to be higher than the strength measured during the tension experiments. For numerical modelling purposes, the Johnson-Cook constitutive model parameters were also evaluated to predict the plastic flow behavior of AA2014-T6 under different strain rates and temperatures. A good agreement between experimental observations and model predictions is observed under different strain rates and different temperatures.